2012
DOI: 10.1890/11-1821.1
|View full text |Cite
|
Sign up to set email alerts
|

Community ecology of invasions: direct and indirect effects of multiple invasive species on aquatic communities

Abstract: Abstract. With many ecosystems now supporting multiple nonnative species from different trophic levels, it can be challenging to disentangle the net effects of invaders within a community context. Here, we combined wetland surveys with a mesocosm experiment to examine the individual and combined effects of nonnative fish predators and nonnative bullfrogs on aquatic communities. Among 139 wetlands, nonnative fish (bass, sunfish, and mosquitofish) negatively influenced the probability of occupancy of Pacific tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 35 publications
5
79
2
1
Order By: Relevance
“…Our results mimic the findings of earlier workers showing negative effects of mosquitofish presence on invertebrates (both zooplankton and macroinvertebrates [26,27,[44][45][46]), often including the near-complete elimination of cladocerans [26,27,44,45]. Our results are also consistent with previous studies that have shown that rotifers escaping fish predation as a result of comparatively very small body size [46] (also see [27]).…”
Section: Discussionsupporting
confidence: 92%
“…Our results mimic the findings of earlier workers showing negative effects of mosquitofish presence on invertebrates (both zooplankton and macroinvertebrates [26,27,[44][45][46]), often including the near-complete elimination of cladocerans [26,27,44,45]. Our results are also consistent with previous studies that have shown that rotifers escaping fish predation as a result of comparatively very small body size [46] (also see [27]).…”
Section: Discussionsupporting
confidence: 92%
“…Of the native species, two are federally protected and are of broad conservation concern ( A. californiense and R. draytonii ), and A. boreas has declined in specific regions (Lannoo 2005). Some populations of these species are currently threatened by invasive species including nonnative fishes and bullfrogs, which potentially act as predators and competitors for native amphibians (Fisher and Shaffer 1996, Lawler et al 1999, Preston et al 2012). Further, widespread cattle grazing in this region has the potential to affect the population dynamics of amphibians at breeding sites directly via trampling, and indirectly by removing vegetation and increasing the concentration of nitrogenous compounds in wetlands (Robins and Vollmar 2002, Roche et al 2012).…”
Section: Study Systemmentioning
confidence: 99%
“…Preston et al (2012) showed the ways in which multiple invaders can directly and indirectly affect such communities. Across 139 wetlands, they determined that introduced fishes and bullfrogs (L. catesbeianus) decrease the probability of occupancy of native Pacific Tree Frogs (Pseudacris regilla) using occupancy models and experimental venues.…”
Section: Reviewsmentioning
confidence: 99%